2020
DOI: 10.1002/ecy.3116
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses of antagonistic and mutualistic networks to agricultural intensification

Abstract: Species interaction networks, which govern the maintenance of biodiversity and ecosystem processes within ecological communities, are being rapidly altered by anthropogenic activities worldwide. Studies on the response of species interaction networks to anthropogenic disturbance have almost exclusively focused on one interaction type at a time, such as mutualistic or antagonistic interactions, making it challenging to decipher how networks of different interaction types respond to the same anthropogenic distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 77 publications
2
21
0
Order By: Relevance
“…There is empirical evidence to support this assertion; Bastolla et al (2009) showed that integrating competition between pollinators in plant-pollinator networks predicts overall species richness better than only considering the mutualistic interaction between pollinators and plants [60]. Data also suggest that anthropogenic land-use change or management interventions have divergent effects on different interaction networks [61], implying that decisions made to enhance, for example, pollination, may inhibit pest control or vice versa.…”
Section: Multilayer Network Community Dynamics and Ecosystem Servicesmentioning
confidence: 99%
“…There is empirical evidence to support this assertion; Bastolla et al (2009) showed that integrating competition between pollinators in plant-pollinator networks predicts overall species richness better than only considering the mutualistic interaction between pollinators and plants [60]. Data also suggest that anthropogenic land-use change or management interventions have divergent effects on different interaction networks [61], implying that decisions made to enhance, for example, pollination, may inhibit pest control or vice versa.…”
Section: Multilayer Network Community Dynamics and Ecosystem Servicesmentioning
confidence: 99%
“…Overall, interaction turnover across sites and seasons exhibited high values and less variable dissimilarity (β wn = 0.87-0.95) compared to species turnover (β s = 0.59-0.99), which reflects the prevalence of interaction rewiring across space and time. A high degree of interaction turnover is common among interaction networks, and similar magnitudes and ranges have been reported primarily for mutualistic, but also antagonistic networks, across spatial (Carstensen et al, 2014;Kemp et al, 2017), temporal (CaraDonna et al, 2017Lepesqueur et al, 2018;Olesen et al, 2011), and land-use gradients (Morrison & Dirzo, 2020). Interaction turnover in plant-herbivore networks has mixed results, Kemp et al (2017) showed that species composition influenced interaction turnover across spatial gradients, while Lepesqueur et al (2018) showed that interaction rewiring is the primary driver of interaction turnover across seasons.…”
Section: Total Interaction Turnover (β Wn ) Versus Species Turnover (β S )mentioning
confidence: 80%
“…There are several nestedness indices, of which nestedness metric based on overlap and decreasing fill (NODF) is considered the most robust [117]. expect that pathogen spread within a pollinator population or interspecific spillover may be reduced or exacerbated by: (i) invasions by novel species or subspecies [17] (Figure 1C); (ii) the extirpation of pre-existing populations or species [62] (Figure 1C); (iii) modification of the relative abundance of species and dominant interactions [63] (Figure 1D); (iv) disruption of species' phenology [64,65] (Figure 1D); (v) shifting species distributions at landscape, regional, or global levels [62]; or (vi) changing species physiology, altering disease resistance, infectivity, or virulence [17,66] (Figure 1E). While scientific and policy awareness of pressures on wild pollinators has increased and led to regulations at various levels protecting pollinators and their habitats, less regulatory…”
Section: Box 1 Key Network Metrics Affecting Pathogen Transmissionmentioning
confidence: 99%
“…Use of herbicides, fertiliser, and destruction of seminatural elements reduce richness and abundance of floral resources providing nectar and pollen [1], which can lead to network generalism [100]. Consequently, plant-pollinator networks in intensively farmed areas tend to be generalised with low modularity and nestedness and high connectance [59,63]. Such a network architecture can either limit or propagate community-wide pathogen transmission (Box 1).…”
Section: Conventional Agricultural Intensificationmentioning
confidence: 99%